Generating Competency-Based Curriculum Conceptual Framework for Nigerian Secondary Schools - Saheed Rufai (IJER (Indonesian Journal of Educational Research), 2021)
Abstract One of the most trending issues of national concern in Nigeria was the revelation by the Vice President of the country, Prof. Yemi Osinbajo that the Federal Government was redesigning school curriculum. He made this statement in the 23rd Convocation Lecture of the Lagos State University on Thursday 16th May, 2019. The details provided by the him concerning the imminent redesigning of the school curriculum arguably suggests a misdirection of education. A deep sense of concern about the implication of a possible misdirection of education in the country with its attendant retrogression and non-attainment of developmental goals constitutes the rationale for a systematic engagement with the official statement. The purpose of this paper is to critically examine the curriculum reforms component of the Convocation Lecture and provide some professional ingredients that were missing therein. The essense is to support the educational enrichment interventions of the Government with appropriate ingredients. In specific terms, the paper seeks to examine the state of secondary education with regard to skills and competencies, assess implication of the Vice President’s oronouncement on imminent school curriculum reform, and formulate a competency-based conceptual framework for secondary schools in the country. Grounded in the philosophical and sociological foundations of education, the paper employs a combination of the philosophical method, observation method, curriculum criticism, document analysis and creative synthesis. Its contribution to scholarship lies in its contextualization of competency-based curriculum conceptual framework designing into the Nigerian context, based on both national and regional peculiarities of the country.